Induction of cellular proliferation in a human astrocytoma cell line by a Trypanosoma cruzi-derived antigen: a mechanism of pathogenesis? - Duran-Rehbein, G. A.; Vargas-Zambrano, J. C.; Cuéllar, A.; Puerta, C. J.; Gonzalez, J. M. (Cellular and Molecular Biology, 2017)
Trypanosoma cruzi can compromise the human central nervous system (CNS) during acute infection or reactivation in immune-suppressed hosts. Astrocytes have been identified as targets of T. cruzi's CNS infection in humans. Despite a high degree of parasitism and cellular lysis by T. cruzi in vitro the number of astrocytoma cells did not change when compared to uninfected cultures. This work evaluated cellular proliferation, changes in Major Histocompatibility Complex (MHC) expression as a reflection of antigen processing, and cytokine (IL-6 & IL-8) secretion in a human astrocytoma cell line exposed to a trypomastigote-derived antigen. Light microscopy was used to evaluate the number of cells; MHC molecule expression, cell cycle and cytokine secretion were assessed by flow cytometry. The number of astrocytoma cells increased proportional to the amount of antigen used and the percentage of cells in G2/M phase was higher when compared to control cultures. Antigen exposure increased expression of MHC class II, but not MHC class I in comparison to cultures incubated without antigen. Astrocytoma cell secretion of IL-6 and IL-8 was unaffected by antigen exposure. These results suggest the participation of a trypomastigote-derived mediator that induces astrocytoma cell proliferation without an inflammatory response; which may contribute to the pathogenesis of neurologic Chagas disease.